Quimera: a simulation platform based on the code Geant4 for dose evaluation in radiotherapy - Alex Cristóvão Holanda de Oliveira; Jose Wilson Vieira; Fernando Roberto de Andrade Lima (Brazilian Journal of Radiation Sciences)
This work describes the development and validation of a simulation platform, called Quimera, based on the Monte Carlo (MC) code Geant4 for dose evaluation in radiotherapy. Quimera consists of two MC applications (qMATphantoms and qNCTphantoms) for dose evaluation from a phase-space and a graphical user interface (qGUI). qMATphantoms is aimed for modeling of physical phantoms used in quality control. NCT phantoms are built from computed tomography (CT) images of patient or physical phantom using a conversion method of CT numbers (NCT). qGUI has the function of creating or editing input files, running the MC applications and ana-lyzing results. MC applications were validated by comparison of dose distributions, whose results were in agreement with the quality assurance standards. qGUI is a differential concerning other Geant4 applications for radiotherapy and can be used for dose distribution analysis from other MC applications. Quimera can be used for research, simple treatment planning and quality assurance in photon beam radiotherapy